Reducing interruptions during medication preparation and administration: An improvement project. Issue 6 (8th July 2019) - Mortaro, Alberto; Pascu, Diana; Pancheri, Serena; Mazzi, Mariangela; Tardivo, Stefano; Bellamoli, Claudio; Ferrarese, Federica; Poli, Albino; Romano, Gabriele; Moretti, Francesca
Abstract : Purpose: According to literature, interruptions during drug administration lead to a significant proportion of medication errors. Evidence on the effectiveness of interventions to reduce interruption is still limited. The purpose of this paper is to explore main reasons for interruptions during drug administration rounds in a geriatric ward of an Italian secondary hospital and test the effectiveness of a combined intervention. Design/methodology/approach: This is a pre and post-intervention observational study based on direct observation. All nurse staff (24) participated to the study that lead to observe a total of 44 drug dispensing rounds with 945 drugs administered to 491 patients in T0 and 994 drugs to 506 patients in T1. Findings: A significant reduction of raw number of interruptions (mean per round from 17.31 in T0 to 9.09 in T1, p <0.01), interruptions/patient rate (from 0.78 in T0 to 0.40 in T1, p <0.01) and interruptions/drugs rate (from 0.44 in T0 to 0.22 in T1, p <0.01) were observed. Needs for further improvements were elicited (e.g. a greater involvement of support staff). Practical implications: Nurse staff should be adequately trained on the risks related to interruptions during drug administration since routine activity is at high risk of distractions due to its repetitive and skill-based nature. Originality/value: A strong involvement of both MB and leadership, together with the frontline staff, helped to raise staff motivation and guide a bottom-up approach, able to identify tailored interventions and serve concurrently as training instrument tool.